Prevalence of celiac disease-specific antibodies and their association with clinical status and environmental factors - de Diego, Gabriel Alejandro (2024)
Background and aims: Celiac disease (CeD) affects 1–2% of the world's population. The aim of this study was to relate the incidence of CeD-related serological markers to symptoms, pathologies, and environmental exposure to wheat flour, given the number of flour mills present in the region. Materials & methods: Serum samples were collected from 537 inhabitants from a rural city. Levels of anti-transglutaminase (a-tTg), anti-gliadin, anti-DGP antibodies and total IgA levels were measured. Volunteers completed a questionnaire covering environmental factors, demographics, pregnancies, other diseases, symptoms, and CeD diagnosis. Geo-referencing of volunteers' homes and mills in the city was performed, and correlations between the different parameters assessed were analysed. Results: A CeD incidence of 1.76 % was found. However, a-tTg and a-gliadin levels were elevated in the population without CeD diagnosis (9.6 % and 30.1 %). Subjects with CD diagnosis showed diarrhoea and colic pain. Women with CeD had fewer pregnancies. Positive a-tTg and number of CeD-associated symptoms appear to correlate with proximity to flour mills. Conclusion: A high prevalence of CeD-related specific antibody positivity in a rural population was found, possibly due to environmental factors related to flour mills. Further research is needed to better understand CeD's pathogenesis and its health implications.